Construction of a competence-based curriculum for internship in obstetrics and gynecology within the medical course at the Federal University of Ceará (Sobral campus) - Linhares, José Juvenal; Dutra, Bárbara de Araújo Lima; Ponte, Maycon Fellipe da; Tofoli, Luis Fernando Farah de; Távora, Priscila Campos Távora; Macedo, Filipe Sancho de; Arruda, Guarany Mont’Alverne de (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: This research project arose from a proposal made to the teachers by the students of a medical course at a federal university in Brazil, from their personal experiences regarding the skills and competencies that should be developed during the obstetrics and gynecology (OBG) stage of the internship. The objective here was to develop the matrix of skills necessary for training good general physicians in the medical course. DESIGN AND SETTING: Exploratory qualitative study conducted in a federal university in Brazil. METHODS: The basis for developing these competencies among OBG interns was “The Competency Matrix for Medical Internship” developed by Bollela and Machado. The instrument was presented to, analyzed by and modified by a set of OBG specialists, at two sessions. RESULTS: The specific competencies expected from students over the internship in OBG were framed within overall topics that had previously been determined and listed: healthcare, decision-making, communication and interpersonal relationships, management and organization of the Brazilian National Health System (Sistema Único de Saúde, SUS) and professionalism. CONCLUSIONS: A competency matrix that standardizes the minimum requirements that interns should be capable of putting into practice after concluding the OBG stage is a valuable tool for ensuring student performance and a fair and rigorous assessment for them, thereby seeking to train good general physicians who meet the community’s needs.